To Compare the Post-operative Pain Following Laser Hemorrhoidoplasty versus Open Hemorrhoidectomy - Babar, Yaseen; Mumtaz, Mohsin; Shah, Munawar; Rehman, Shahana (Indus Journal of Bioscience Research, 2025)
Objectives: To compare postoperative pain between laser hemorrhoidoplasty and open hemorrhoidectomy. Materials and Methods: This randomized controlled trial was conducted at the multiple centers including Yashfeen General Hospital Peshawar, Mumtaz Surgimed Hospital Vehari, Khushal Medical Centre Peshawar and Muhammad Teaching Hospital Peshawar, Pakistan, from 15 February 2024 to 15 August 2024 with approval from the hospitals’ ethical boards and research committees. Patients meeting the inclusion criteria and providing written informed consent were enrolled. A total of 60 patients were randomized into two groups: Group A underwent Laser hemorrhoidoplasty, while Group B received Open Hemorrhoidectomy. Follow-up was conducted on day 3, assessing primary (pain) and secondary outcomes (hospital stay, wound infection, postoperative bleeding, procedure duration, itching, and mucus discharge) using a structured questionnaire. Data analysis was performed using SPSS version 25. Results: The mean age was 37.87±11.27 years, with 61.7% aged 18-40 years. Males comprised 51.7% and females 48.3%. The mean pain score was lower in Group A (2.43±1.10) than in Group B (5.43±1.54) (p=0.00). Wound infection (36.7% vs. 10.0%, p=0.015), bleeding (30.0% vs. 0%, p=0.00), itching (46.7% vs. 13.3%, p=0.00), and mucus discharge (40.0% vs. 10.0%, p=0.00) were significantly higher in Group B. Conclusion: Laser hemorrhoidoplasty significantly reduces postoperative pain, requires less analgesia, and speeds up recovery compared to open hemorrhoidectomy. However, the choice of procedure should consider patient needs, surgeon expertise, and available resources. Further research is needed to assess its long-term efficacy.